The Analysis of Modal Auxiliary Verb Used in City of Heavenly Fire Novel Written By Cassandra Clare - I Gusti Ngurah Bagus Yoga Widiadnya (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2023)
Language use in novel accordance with the context of sentence and according to events that occur in the story such as direct sentences and indirect sentences. The purposes of this study are to know the kinds of modal auxiliary verb and the function used in City of Heavenly Fire Novel written by Cassandra Clare. This study is descriptive qualitative research and object discussed about City of Heavenly Fire Novel written by Cassandra Clare. The data collection techniques are observation and literature review. Data analysis is to analyze sentences that use modal auxiliary verbs in the novel. The research findings are (1) modal auxiliary verb â€œcouldâ€ and â€œwouldâ€ mostly used in City of Heavenly Fire Novel, the use of modal auxiliary verbs â€œcouldâ€ and â€œwouldâ€ is 62% more than the use of modal auxiliary verb â€œwillâ€ and â€œcanâ€; (2) The functions of modal auxiliaries are expressing present and past ability, expressing expectation, requesting action, requesting action, requesting permission, requesting permission, expressing preference, expressing present need or lack of need, expressing past need or lack of need, expressing advice, expressing advice about the past (action not taken), expressing present and past possibility, and expressing probability.